Public understandings of potential policy responses to health inequalities: Evidence from a UK national survey and citizens' juries in three UK cities. (December 2021) - Smith, K.E.; Macintyre, A.K.; Weakley, S.; Hill, S.E.; Escobar, O.; Fergie, G.
Abstract: A substantial body of research describes the distribution, causes and potential reduction of health inequalities, yet little scholarship examines public understandings of these inequalities. Existing work is dominated by small-scale, qualitative studies of the experiences of specific communities. As a result, we know very little about what broader publics think about health inequalities; and even less about public views of potential policy responses. This is an important gap since previous research shows many researchers and policymakers believe proposals for 'upstream' policies are unlikely to attract sufficient public support to be viable. This mixed methods study combined a nationally representative survey with three two-day citizens' juries exploring public views of health inequalities and potential policy responses in three UK cities (Glasgow, Manchester and Liverpool) in July 2016. Comparing public opinion elicited via a survey to public reasoning generated through deliberative processes offers insight into the formation of public views. The results challenge perceptions that there is a lack of public support for upstream, macro-level policy proposals and instead demonstrate support for proposals aiming to tackle health inequalities via improvements to living and working conditions, with more limited support for proposals targeting individual behavioural change. At the same time, some macro-economic proposals, notably those involving tax increases, proved controversial among study participants and results varied markedly by data source. Our analysis suggests that this results from three intersecting factors: a resistance to ideas viewed as disempowering (which include, fundamentally, the idea that health inequalities exist); the prevalence of individualising and fatalistic discourses, which inform resistance to diverse policy proposals (but especially those that are more 'upstream', macro-level proposals); and a lack of trust in (local and national) government. This suggests that efforts to enhance public support for evidence-informed policy responses to health inequalities may struggle unless these broader challenges are also addressed. Highlights: The UK public favour tackling health inequalities via living and working conditions. Individual and macro-economic responses are also supported but more controversial. Fatalism, low trust in government & resistance to disempowerment inform controversy. Different data provide distinct insights, underlining importance of mixed methods. Support for macro-economic responses was highest in collective ranking exercise.